Comparative analysis of meat quality and flavor profiles between Bian chicken and Cobb broiler using FTIR and GC×GC-TOF MS technologies - Zhang, Bochi; Zhao, Rui; Zhang, Kai; Yu, Wenjie; li, Kaige; Yang, Chunlei; Du, Liying; Guo, Kai; Song, Xianyi (Frontiers in Nutrition, 2025)
This study systematically compared meat quality characteristics and flavor profiles between the local Shanxi breed Bian chicken (BIAN) and the commercial Cobb broiler (CB) using a comprehensive analytical approach. In terms of physical properties, Bian chicken exhibited significantly lower pH values (5.64 vs. 5.95; p = 0.026) and shear force (2.11 vs. 2.86 kg; p = 0.016), as well as a higher yellowness value b* (7.37 vs. 5.66; p = 0.029), indicating better tenderness and meat color characteristics. Fourier transform infrared (FTIR) spectroscopy revealed fundamental differences in biomolecular composition and protein secondary structure between the two breeds. Specifically, Bian chicken showed higher α-helix content (37.54% vs. 33.50%), whereas Cobb had higher β-sheet content (35.45% vs. 32.39%) and greater total lipid (18.39% vs. 15.36%). These structural differences corresponded with the observed variations in meat quality traits. Comprehensive two-dimensional GC–TOF MS analysis showed that Bian chicken contained 2,150 volatile flavor compounds (including all detected isomeric forms), of which 1,068 were unique to Bian. The aldehyde content in Bian (15.13%) was notably higher than in Cobb (10.52%), and these low-threshold aroma compounds are crucial for a rich, meaty aroma. Differential compounds such as (E)-2-nonenal, 2-pentylfuran, heptanal, and 1-octen-3-ol were identified by multivariate analysis as potential markers distinguishing the two breeds. Sensory evaluation indicated that Bian chicken has more pronounced flavor characteristics, consistent with its unique compound profile. This study reveals significant biological differences in meat quality and flavor profiles between Bian chicken and Cobb broiler, demonstrating that Bian chicken possesses distinctive quality attributes including superior tenderness, unique protein structural characteristics, and a richer flavor profile dominated by key aroma compounds. These findings provide crucial scientific evidence for the conservation of indigenous breed characteristics, quality standardization, and market differentiation of Bian chicken, supporting its sustainable development and commercial valorization.